2019
DOI: 10.1016/j.jamcollsurg.2018.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Surgical Access: A Systematic Literature Review, Conceptual Model, and Evidence Map

Abstract: Healthcare disparities in quality represent one of the greatest challenges in achieving uniformly high-quality care (1). Research reporting disparities in surgical outcomes are abundant (2-6). The cornerstone of delivering high quality healthcare is ensuring optimal access for all patients. A relative lack of access to surgical services may be a contributing factor to disparities in surgical outcomes.Access is "the timely use of personal health services to achieve the best possible outcomes" (7). Utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 237 publications
0
111
0
Order By: Relevance
“…A framework for understanding healthcare disparities can be conceptually understood through three distinct measures: (1) indication detection, (2) progression to surgery, and (3) receipt of optimal care. 10 Using this model, the rate of cochlear implantation qualification can be considered a surrogate for candidacy referral since a notably high cochlear implantation qualification rate is potentially indicative that referral for evaluation is occurring at a more advanced stage of hearing loss (ie, delayed referral). In other words, if everyone who is screened for a cochlear implant qualifies, there is a high likelihood that patients who are borderline cochlear implant candidates are not being referred for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…A framework for understanding healthcare disparities can be conceptually understood through three distinct measures: (1) indication detection, (2) progression to surgery, and (3) receipt of optimal care. 10 Using this model, the rate of cochlear implantation qualification can be considered a surrogate for candidacy referral since a notably high cochlear implantation qualification rate is potentially indicative that referral for evaluation is occurring at a more advanced stage of hearing loss (ie, delayed referral). In other words, if everyone who is screened for a cochlear implant qualifies, there is a high likelihood that patients who are borderline cochlear implant candidates are not being referred for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data report higher obesity rates in African Americans and Hispanics compared with white, non-Hispanics in the United States [1]. Given similarities in socio-economic factors between AAs and Hispanics, and the racial disparities that exist in access to health care, education, and/or insurance [31], it would be of great interest to utilize the MBSAQIP to examine potential similarities and/or differences in underlying comorbidities and perioperative outcomes…”
Section: Discussionmentioning
confidence: 99%
“…We also found that children from households with a primary language other than English experience disparity in surgery care. Access barriers related to language, insurance status, and lack of a usual source of health care can add to the disparity faced by minority children 22 ; thus, the adjusted odds ratio for Hispanic children which was higher relative to unadjusted rates may underestimate the true extent of the disparity experienced by this population 18 . Although prior studies found differences by income, when adjusting for other salient socioeconomic factors related to healthcare access, such as insurance status and language, income was not an independent predictor of the rate of pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While these data cannot differentiate whether disparities occurred in critical vs. noncritical surgeries or whether these disparities yielded poorer outcomes, prior studies demonstrate disparities in rates as well as outcomes of a range of critical surgery procedures, from emergent procedures such as appendectomy to specialized procedures such as craniosynostosis repair, spinal fusion, and neuro‐oncologic surgeries 1‐3,6,16,17 . De Jager et al developed a conceptual model of disparities in surgical access, highlighting four levels of access barriers: provider access, detection of a surgical indication, progression to surgery, and receipt of optimal care 18 . While the majority of research has been conducted in adults, studies detecting disparities in pediatric surgical conditions were identified at each of these levels.…”
Section: Discussionmentioning
confidence: 99%